2005
DOI: 10.1021/jf048957z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhodium Heterogeneous Catalyst and Isomerization Conditions on Linoleic Acid Conjugation of Soybean Oil

Abstract: Rhodium heterogeneous catalyst was used to catalyze isomerization of linoleic acid in soybean oil to conjugated linoleic acid (CLA). A central composite rotatable design with five levels of three variables, namely, reaction temperature, stirring speed, and reaction time, was used to determine the maximum CLA yield. The formation of CLA during isomerization was greatly dependent on the reaction temperature and time. The CLA content of soybean oil increased from 0.63 to 202.42 mg/g oil when isomerization was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…However, the composition of CLA isomers also varies with the temperature. This tendency was also reported by Pakdeechanuan et al (2005) when they hydrogenated soybean oil over 5% Rh/C catalyst. According to Table 2, the trans/trans CLA isomer concentration clearly increased when the temperature increases from 180 to 210 • C, whereas both 9-cis, 11-trans C18: 2 and 10-trans, 12cis C18: 2 health beneficial CLA isomers, attained a concentration of ca.…”
Section: Temperature Effectsupporting
confidence: 76%
“…However, the composition of CLA isomers also varies with the temperature. This tendency was also reported by Pakdeechanuan et al (2005) when they hydrogenated soybean oil over 5% Rh/C catalyst. According to Table 2, the trans/trans CLA isomer concentration clearly increased when the temperature increases from 180 to 210 • C, whereas both 9-cis, 11-trans C18: 2 and 10-trans, 12cis C18: 2 health beneficial CLA isomers, attained a concentration of ca.…”
Section: Temperature Effectsupporting
confidence: 76%
“…Homogeneous and heterogeneous metal catalysts, enzymes, and photocatalysts have been used to conjugate vegetable oil. For a laboratory scale, it was convenient to use a catalyst previously report by Larock and coworkers .…”
Section: Discussionmentioning
confidence: 99%
“…With an average of 4.5 double bonds per triglyceride,10 soybean oil is only moderately active toward free radical species, but the reactivity can be considerably increased by the conjugation of the carbon–carbon double bonds of the fatty acid chains. Several studies regarding the double‐bond isomerization of vegetable oils have been reported in the literature 16–19. Our group has developed a homogeneous isomerization procedure employing [RhCl(C 8 H 14 ) 2 ] 2 as a precatalyst 20.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies regarding the double-bond isomerization of vegetable oils have been reported in the literature. [16][17][18][19] Our group has developed a homogeneous isomerization procedure employing [RhCl(C 8 H 14 ) 2 ] 2 as a precatalyst. 20 The reaction yields >95% conjugation for several vegetable oils tested and has been frequently used in our work on bioplastics.…”
Section: Introductionmentioning
confidence: 99%